Treatment of retinopathy of prematurity in extremely premature infants over an 18‐year period. (18th March 2013) - Gunn, David J; Cartwright, David W; Yuen, Sonia A; Gole, Glen A
Abstract : Background:  To report the efficacy of laser diode therapy in the treatment of retinopathy of prematurity (ROP) in extremely premature (EP) infants over an 18‐year period. Design:  Retrospective study. Participants:  One hundred twenty‐eight eyes in 66 infants treated between 23 and 25.6 weeks. Methods:  Five hundred fifty‐four infants between 23 and 25.6 weeks gestational age (GA) were admitted to The Royal Brisbane and Women's Hospital Neonatal Intensive Care Unit (NICU) between 1992 and 2009. Three hundred seventy‐three patients survived to undergo screening, 304 were diagnosed with ROP, and 66 infants required diode laser therapy. Main Outcome Measures:  Success of treatment, visual and refractive outcomes. Results:  One hundred twenty‐eight eyes from 66 infants (18.8% of those screened) underwent laser treatment with a mean GA of 24.3 weeks and mean birth weight of 711.4g. Fifty‐six eyes were treated at pre‐threshold disease, and 72 eyes at threshold disease. Over the study period, the number of laser spots and regression rate of ROP increased, while the frequency of re‐treatment decreased. At 40 weeks, 119 eyes had regressed ROP (93%), two advanced to stage 4a, three to stage 4b and four to stage 5. Aggressive posterior ROP (AP‐ROP) occurred in 15 eyes (11.7% of those treated). Forty‐three patients (65%) were followed up for a mean of 56.5 months. The number of laser spots correlated well with subsequent refractive error but poorly with corrected visual acuity. Conclusions:  In EP infants, laser diode therapy is an effective technique to halt the progression of ROP in most cases. AP‐ROP is uncommon, even in this subgroup of extremely premature infants.